External technology supply and client-side innovation - Christian Peukert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Flexibility in response to competitive pressure from globalized markets and increasingly individualized customer desires has become vital for firms. A common strategy to address this challenge is to employ a dynamic concept of organization and reach beyond the boundaries of the firm. Accordingly, technology transfer from providers of knowledge intensive business services attracts more and more attention. In this context we focus on external supply of information technology and client-side innovation. The aim of this paper is to contribute to resolving an empirical puzzle arising from the prior literature. Some authors find beneficial effects of IT outsourcing, others underline that firms often fail to achieve expected strategic goals. Our stylized theoretical model combines a knowledge production function framework and transaction cost economics. We hypothesize that the right balance between internal and external knowledge is critical for innovation. The empirical application is German firm-level data covering a wide range of industries from 2003 to 2006. Our results largely support the theoretical arguments and suggest a positive linear relationship between the level of outsourcing and process innovation. For product innovation we find a hump-shape.
Keywords: L24; D23; O31; 330; knowledge production function; transaction cost economics; product innovation; process innovation; KIBS; IT outsourcing; ZEW ICT survey; Innovation; Informationstechnik; Outsourcing; Technologietransfer; Unternehmensdienstleistung; Wissen; Produktionsfunktion; Transaktionskosten; Deutschland